Project EmpreedeTIMOR: how to promote entrepreneurship among students? - Xavier, Tomas (2014)
Entrepreneurship has been recognized as a critical factor in promoting innovation, productivity, creating employment opportunities and economic development of a country. In the current environment it is important for a young country like East Timor to promote entrepreneurship as a key opportunity, in order to increase the number of individuals with individual initiative, i.e. entrepreneurs who take responsibility for economic development and job creation for the working population. The present study aims to understand the attitudes and values of the East Timorese students in relation to entrepreneurship. Taking as a starting point a survey set to study the potential of entrepreneurship among university students in East Timor, the paper presents and discusses the results obtained on various issues such as entrepreneurial intention, predisposition, risk disposition, and personality traits and skills. Our sample involves 140 students from National University of East Timor. The students report good entrepreneurial intentions, good levels of risk disposition, and high levels of self-efficacy, endurance and autonomy. They also report good perceived levels of technical skills but admitted lower perceived financial skills. Several differences were identified concerning students’ gender, course or having self-employed parents. The study indicated a high entrepreneur potential among East Timorese university students.